Micro-techniques for analysis of human adipose tissue fatty acid composition in dietary studies - Hodson, L; Neville, M; Chong, M; Rogers, I; Huda, S; Freeman, D; Frayn, K; Fielding, B (Elsevier, 2013)
Background and aims: Adipose tissue (AT) fatty acid (FA) composition is considered to be the gold standard long-term biomarker of dietary fatty acid intake. Typically this measurement is made directly from samples collected via large-needle-biopsy or incision. However, with growing interest in the role of AT in relation to health, ideally the fatty acid composition would be analysed along with other measurements, such as gene expression or histology, on a single AT sample. Here we assess alternative ways of obtaining AT for measuring FA composition, in some cases in conjunction with other measurements. Methods and results: The FA composition of tissue obtained via different methods was compared to that of tissue collected via large-needle or surgical biopsy. Fatty acid composition was not significantly different in AT collected by small-needle mini-biopsy (n=10), from an RNA 'lipid layer' (obtained during RNA extraction, 2 sites, n=6 for each), or from cryosectioned tissue prepared for histology (n=10). We also assessed the usefulness of the composition of plasma NEFA as a surrogate marker of subcutaneous AT (n=58-80). Most FAs in plasma NEFA correlated strongly with those in AT (P<0.05). Conclusion: It is feasible to measure the FA composition of AT on very small amounts of tissue. Additionally, it is possible to measure FA composition on the lipid rich 'by-product' of AT samples undergoing RNA extraction for gene expression. Samples sectioned for histology are also suitable. This provides further opportunities for multidisciplinary collaborations that may lead to a better application of dietary biomarkers. © 2012 Elsevier B.V.